Anti-inflammatory liposomes have no impact on liver regeneration in rats. Issue 4 (December 2015) - Jepsen, Betina Norman; Andersen, Kasper Jarlhelt; Knudsen, Anders Riegels; Nyengaard, Jens Randel; Hamilton-Dutoit, Stephen; Svendsen, Pia; Etzerodt, Anders; Møller, Holger Jon; Moestrup, Søren Kragh; Graversen, Jonas Heilskov; Mortensen, Frank Viborg
Abstract: Introduction: Surgical resection is the gold standard in treatment of hepatic malignancies, giving the patient the best chance to be cured. The liver has a unique capacity to regenerate. However, an inflammatory response occurs during resection, in part mediated by Kupffer cells, that influences the speed of regeneration. The aim of this study was to investigate the effect of a Kupffer cell targeted anti-inflammatory treatment on liver regeneration in rats. Methods: Two sets of animals, each including four groups of eight rats, were included. Paired groups from each set received treatment with placebo, low dose dexamethasone, high dose dexamethasone or low dose anti-CD163 dexamethasone. Subsequently, the rats underwent 70% partial hepatectomy. The two sets were evaluated on postoperative day 2 or 5, respectively. Blood was drawn for circulating markers of inflammation and liver cell damage; liver tissue was sampled for analysis of regeneration rate and proliferation index. Results: The high dose dexamethasone group had significantly lower body and liver weight than the placebo and anti-CD163-dex groups. There were no differences in liver regeneration rates between groups. Hepatocyte proliferation was completed faster in the placebo group, although this was not significant. The anti-CD163-dex group showed increased blood levels of albumin and alanine aminotransferase and a diminished inflammatory response in terms of significantly reduced haptoglobin, α2-macroglobulin and Interleukine-6. Conclusion: Low dose dexamethasone targeted to Kupffer cells does not affect histological liver cell regeneration after 70% hepatectomy in rats, but reduces the inflammatory response judged by circulating markers of inflammation. Highlights: Use of anti-CD163-dexamethasone is an attractive strategy for anti-inflammatory treatment. In the present study the impact of anti-CD163 dexamethasone on liver regeneration in rats was studied. We show that low dose anti-CD163 dexamethasone has no negative effect on liver regeneration after 70% hepatectomy in rats. Characters should then be down to 122.